On Reciprocal Series of Generalized Fibonacci Numbers with Subscripts in Arithmetic Progression - Neşe Ömür (Discrete Dynamics in Nature and Society)
We investigate formulas for closely related series of the forms: ∑∞𝑛=01/(𝑈𝑎𝑛+𝑏+𝑐), ∑∞𝑛=0(−1)𝑛𝑈𝑎𝑛+𝑏/(𝑈𝑎𝑛+𝑏+𝑐)2, ∑∞𝑛=0𝑈2(𝑎𝑛+𝑏)/(𝑈2𝑎𝑛+𝑏+𝑐)2 for certain values of 𝑎, 𝑏, and 𝑐.